(untitled) (Vietnam Journal of Community Medicine, 2023)
Objective: Evaluation of the early results of balloon dilation angioplasty of Peripheral pulmonary artery stenosis. Subjects and methods: From January 2021 to August 2022, all patients diagnosed with Peripheral pulmonary artery stenosis who underwent balloon dilation were retrospectively studied. Results: A total of 31 patients were in the study. The age of the patients in the study group was from 3.8 months to 12 years, the median weight was 15.6%. All patients were after cardiac surgery, specially post-operation of pulmonary atresia -a ventricular septal defect - unifocalization of collaterals (45.2%). The success rate was 58.1% (18/31). Threepatients developed complications after the intervention (9,7%),includingtwowith balloon rupture and onewith premature ventricular contractions. The difference between before and after intervention in pulmonary artery diameter (3.4 ± 1.3 and 5.6 ± 1.6 mm), right ventricle systolic pressure (60.1 ± 16.1 and 50.3 ± 13.8 mmHg), maximum pressure gradient (24.7 ± 11.6 and 14.7 ± 9.4 mmHg), p < 0.001. Conclusions: Balloon dilation angioplasty of Peripheral pulmonary artery stenosis has good initial results.